2000
DOI: 10.1385/endo:12:3:295
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Disrupting Cell Contact on the Nuclear Accumulation of β-Catenin and Subsequent Apoptosis of Rat Ovarian Surface Epithelial Cells In Vitro

Abstract: The present studies were designed to determine how disrupting cell contact induces rat ovarian surface epithelial cells (i.e., ROSE-179 cells) to undergo apoptosis. In the first series of studies, the effect of depleting serum and calcium on the levels of the adhesion proteins N-cadherin and beta-catenin was examined. These studies revealed that the depletion of serum and calcium results in the degradation of N-cadherin but not beta-catenin. However, the localization of beta-catenin changed from principally th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Previous studies have shown that cells infected with C. trachomatis become resistant to apoptotic stimuli (21,22). At the same time, other studies have shown that the release of ␤-catenin from junctional complexes into the cytosol may be an important step in the initiation of apoptotic death in several types of cells (3,15,20,29,46,60,62). Perhaps, by binding ␤-catenin and disrupting one of the pathways that leads to apoptotic cell death, C. trachomatis might prolong the life of the infected cell so that the organism can develop and mature.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that cells infected with C. trachomatis become resistant to apoptotic stimuli (21,22). At the same time, other studies have shown that the release of ␤-catenin from junctional complexes into the cytosol may be an important step in the initiation of apoptotic death in several types of cells (3,15,20,29,46,60,62). Perhaps, by binding ␤-catenin and disrupting one of the pathways that leads to apoptotic cell death, C. trachomatis might prolong the life of the infected cell so that the organism can develop and mature.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, with neoplastic progression, the tendency of OSE to undergo epithelio‐mesenchymal conversion diminishes and the cells become increasingly committed to complex epithelial phenotypes which include the formation of glandular structures and papillae (1,4,13,14) . They also acquire the epithelial adhesion molecule E‐cadherin which may act as a survival factor (15–17) and increased expression of the receptor for hepatocyte growth factor ( c‐met ) which contributes to the growth and invasiveness of many forms of cancer (18) . The stability of these epithelial phenotypes under a variety of conditions in vivo and in culture most likely reflects a form of autonomy, ie, unresponsiveness to environmental controls, which is one of the hallmarks of neoplastic cells.…”
Section: Biology Of Osementioning
confidence: 99%
“…It is known that β-catenin, which associates with the intracellular domain of cadherin on the cell membrane, is released from cadherin and sends a signal to the nucleus, when cadherin-mediated cell–cell contact is disrupted by calcium depletion [15]. In the newt, RPE cells express N-cadherin ([12]; see below).…”
Section: Resultsmentioning
confidence: 99%